Assessing consumer empowerment and influencing factors in Central Bangka Regency: a multidimensional approach - Muhammad Faisal Akbar; Devi Valeriani; Panggio Restu Wilujeng; Mustofa Tohari (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
The rapid development of trade technology in Indonesia exposes consumers to potential exploitation during purchasing. This study examines consumer empowerment in Central Bangka Regency using primary data from 88 respondents across four districts. The Consumer Empowerment Index (CEI) value of 38.53, classified as "understand," indicates a fundamental grasp of rights and obligations and reveals room for growth in consumer empowerment. The analysis shows higher empowerment during the purchase phase, with informed decision-making and support for local businesses. However, a weakness emerges in the post-purchase phase, as consumers are less likely to voice experiences or criticize unsatisfactory products, potentially impacting product quality and customer satisfaction. Regression analysis reveals that only years of schooling and age significantly influence the CEI, while the location of residence, gender, and income group do not have significant effects. The model's low R-squared value suggests potential refinement through additional variables or research. These findings provide valuable insights for the government and stakeholders to enhance Central Bangka Regency's consumer empowerment. Focusing on increasing consumer awareness and engagement in the post-purchase phase through targeted educational campaigns, consumer rights workshops, and accessible complaint channels is essential. However, it is crucial to recognize that observed associations do not imply causation and further research is required to establish causal relationships and explore other factors contributing to consumer empowerment.